Application of the trait-Factor theory-Based vocational preference inventory on the government school counsellors in Malaysia - Mohd Saufi, Nor Salahfiah; Yunus, Ahmad Rozelan; Abdullah, Norida; Mat, Zawiah; Ishak, Nurul Huda; Ahmad Rozelan, Aina Dalila (Arts and Science Press Pte. Ltd., 2025)
The study aimed to develop a reliable module of career counselling based on the trait-factor theory for government school counsellors in Malaysia. Known as the Modul Kaunseling Kerjaya Tret dan Faktor (MKKKTF), this module was adapted from the Model Pembinaan Modul Sidek (MPMS) and integrated with the trait-factor theorem guidelines. To determine the module’s validity, the content and the module’s appropriateness and significance were evaluated and reviewed by a group of panel experts who were selected using a specific list of criteria. Using the Fuzzy Delphi Technique, the experts’ responses and evaluation of MKKKTF were analysed, and the findings revealed that the MKKKTF was significantly variable to be used as a guideline for government school counsellors, including those who are not registered with the Kaunselor Berdaftar Perakuan Amalan (KBPA) in Malaysia.